Republic of Moldova : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2004)
This Joint Staff Advisory Note (JSAN) reviews Moldova's Economic Growth and Poverty Reduction Strategy Paper (EGPRSP) Progress Report. Moldova's EGPRSP is an important step toward achieving sustainable economic growth and poverty reduction. This JSAN highlights key characteristics of the EGPRSP. It provides IMF staff advice on key priorities for strengthening the EGPRSP and for ensuring effective implementation. It also highlights several critical areas where current policies do not match those articulated in the EGPRSP.